PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN MENYIMAK DIKELAS VI SEKOLAH DASAR - Jusmeri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Listening is one of the activities someone carries out to get and add new information or new knowledge. In terms of listening, students tend to listen but do not understand the content that is listened to. Students tend to underestimate listening, especially listening to factual problems. One of the efforts that will be made to improve students' listening skills is to use audio-visual media. The research used Classroom Action Research (CAR) using a research design model of Kemmis and Mc. Taggart. This research was conducted at SD Negeri 006 Sungai Ara. The subjects of this study were students of class VI (Six); the number of students was 24. Two cycles showed students' listening learning outcomes with an increasing average. In the first cycle, the averages obtained before and after using audio-visual media were 71.33 and 76.63. In the second cycle, the averages obtained before and after using audio-visual media were 76.42 and 79.46. Thus, the application of audio-visual media improved students' listening skills and students' learning interests